Impact of VACTERL Association and Chromosomal Anomalies on Outcomes After Esophageal Atresia Repair: Insights from the EUPSA Registry - Soyer, Tutku; Pederiva, Federica; Dalena, Paolo; Pio, Luca; Kakar, Mohit; Hall, Nigel J.; Morini, Francesco; Esophageal Atresia Registry participants; Sindjic-Antunovic, Sanja; Conforti, Andrea; Bagolan, Pietro; Lilja, Helen Engstrand; Ehren, Henrik; Rolle, Udo; Radojicic, Zoran; Lukac, Marija; Oomen, Matthijs; Gamba, Pier Giorgio; Leon, Francesco Fascetti; Blaauw, Ivo de; Scharbatke, Horst; Wijnen, Rene; Till, Holger; Friedmacher, Florian; Bockanic, Lubomir; Gocik, Michel; Minaev, Sergey V.; Muntean, Liviu; Mironescu, Aurel; Rintala, Risto; Khairy, Hussein; ElFiky, Mahmoud; Riccipetitoni, Giovanna; Costanzo, Sara; Chiesa, Pierluigi Lelli; Lisi, Gabriele; Tovar, Juan A.; Martinez, Leopoldo; Prato, Alessio Pini; Casaccia, Germana; Ure, Benno; Kuebler, Joachim; Snajdauf, Jiri (European Journal of Pediatric Surgery, 2025)
Although VACTERL association is a recognized entity in patients with esophageal atresia (EA), its impact on surgical outcomes remains unclear. This study aimed to evaluate the influence of VACTERL association and chromosomal anomalies (VACTERL-CA) on the surgical outcomes of EA patients, offering novel insights into risk stratification.All patients enrolled in the European Pediatric Surgeons' Association (EUPSA) Esophageal Atresia Registry (EAR) between July 2014 and December 2017 were included. Patients were classified into two groups: those with VACTERL-CA and those without these anomalies (non-VACTERL). Groups were compared for demographics, associated malformations, surgical approach, complications, and outcomes.Among 372 patients, 22% (n = 82) were classified as VACTERL-CA. This group had significantly lower gestational age (35.9 weeks vs. 37.1 weeks, p = 0.004), birth weight (2,312 g vs. 2,663 g, p < 0.001), and APGAR scores at 5 and 10 minutes (p = 0.005). Surgical strategies, including rates of primary anastomosis (88% in both groups), did not differ. Anastomotic leak and stricture rates were similar; however, recurrent fistula was more common in VACTERL-CA (4.9% vs. 1.0%, p = 0.023). Overall mortality was higher in VACTERL-CA (14.6% vs. 5.2%, p = 0.003), largely due to associated anomalies such as cardiac or neurologic conditions, whereas EA-related mortality was more frequent in non-VACTERL (1% vs. 0%). Sepsis was also more frequent in VACTERL-CA (10.9% vs. 4.5%, p = 0.033). In multivariate analysis, low birth weight (adjusted odds ratios [aOR]: 0.95 per 100 g, p = 0.010) and cardiac malformations (aOR: 2.33, p = 0.002) were independently associated with VACTERL-CA.EA patients with VACTERL-CA represent a high-risk subgroup characterized by prematurity, major cardiac defects, and increased sepsis risk. These findings highlight the need for early cardiac screening, standardized infection-prevention bundles, and tailored multidisciplinary care to improve survival and reduce preventable complications.
Keywords: esophageal atresia; VACTERL; chromosomal anomalies; outcome; tracheoesophageal fistula